English syntax : - Radford, Andrew (Cambridge University Press, 2004)
This abridged version of Radford's Minimalist Syntax: Exploring the Structure of English offers a concise, accessible introduction to current syntactic theory, drawing on the key concepts of Chomsky's Minimalist Program. Assuming little or no prior grammatical knowledge, it leads students through a range of topics in English syntax, beginning at an elementary level and progressing in stages towards more advanced material. An extensive glossary is included and each chapter contains a workbook section with "helpful hints", exercises, and model answers, suitable for class discussion and self-study.